Analisa Terhadap Pelayanan Kantor Kementerian Agama Kabupaten Pinrang Dalam Meningkatkan Kepuasan Jamaah Haji - Nurfitriyani Ismail; Muhammad Saleh; Muhammad Haramain (Jurnal Kajian Manajemen Dakwah, 2021)
This study discusses the analysis of the services of the Ministry of Religion of Pinrang Regency in increasing the satisfaction of pilgrims. This type of research is qualitative. Collecting data using observation, interview, and documentation techniques. While the data analysis techniques used are data reduction, data presentation and drawing conclusions. The results showed that: (1) The Office of the Ministry of Religion of Pinrang Regency has provided forms of congregational services, namely administrative services such as registration of prospective pilgrims for Hajj and cancellation of Hajj, guidance for Hajj rituals, transportation services, accommodation services, consumption services, and health services. (2) The satisfaction of prospective pilgrims with services at the Office of the Ministry of Religion of Pinrang Regency, namely the community is very satisfied with the services provided to prospective pilgrims who come to the office to register prospective pilgrims and so on. Employees at the Pinrang Regency Ministry of Religion in serving the community are also friendly and polite in speaking. The facilities and infrastructure at the Pinrang Regency Ministry of Religion are quite good